Attitudes of interior spaces that contribute to videoconferencing fatigue among selected college students - Castro, Ysabel Louise (University of the Philippines Diliman, 2023)
The concept of living space drastically changed due to the pandemic and how people adapted to the work-from-home setups including remote learning. The purpose of the study is to describe the attributes of interior spaces that contributed to videoconferencing fatigue and its correlation. The study used a quantitative descriptive research design that utilizes purposive and convenience sampling. Thirty (30) students based on the criteria developed by the researcher qualified for the online survey. A quantitative data analysis focusing on the frequency of responses using a thematic analysis was utilized. Results showed that the most common physiological issue relates to posture, specifically the back and neck. Moreover, the most common spatial issue relates to lack of adequate lighting and unsuitable location of the eremote learning setup. The respondents addressed these issues through improving the quality and dimensions of their furniture , as well as their access to proper lighting and a more efficient location of their setup. The study concludes that there is a direct correlation between the furniture and spatial design to the physiological and spatial well-being. Based on he likert scale, the physiological improvements were significant after the changes were made. The findings in this study will be beneficial to designers, furniture manufacturers, and homeowners as it will serve as a guide on how to curate and reconfigure existing spaces to have a conducive space for remote learning and explore non-COVID-19-related health issues. The study also provides data for the educational sector on the significant effects of synchronous classes to physical well-being despite the absence of physical contact.